HYDROGEOLOGICAL, HYDROGEOCHEMICAL CHARACTERISTICS AND HYDROGEOCHEMICAL PROFILES IN COASTAL AREA IN VIETNAM - Dan, Nguyen Van; Huy, Trieu Duc; Quyen, Pham Ba; Hung, Tran Duy; Linh, Van Thuy; Dao, Phung Anh; Dung, Dao Van (Vietnam Journal of Marine Science and Technology, 2015)
Vietnam has a long coastal line along which there are many plains that are composed of unconsolidated Kainozoic sediments in 5 granular aquifers overlying fissured ancient rock. The Holocene unconfined aquifer (qh) at the top of the profile contains fresh water lens with small potential water reserves. The Pleistocene (qp) and Neocene aquifers are confined with wide distribution and complicated hydrogeochemical condition: saline water in most areas, fresh water in small areas. There are 4 typical hydrogeochemical profiles in coastal areas: (I) fresh water in the whole profile, (II) fresh water in the upper part and saline water in the lower part, (IV) saline water in the whole profile, and (V) saline water in the upper part and fresh water in the lower part. Profiles (I), (II), (V) have effective use for drinking water. The profile type (Ib) has distribution in Thach Khe-Ha Tinh, Quang Tri and Thua Thien-Hue, (V) has distribution in Nam Dinh, Tra Vinh, Soc Trang, Bac Lieu, Ca Mau and South-East of Kien Giang in which the fresh water can be in shallow onshore areas.